TECHNICAL SCIENTIFIC PROGRESS AND SOCIETY DEVELOPMENT - Adina TĂTAR (Fiabilitate şi Durabilitate)
This paper conducts a study on the role of science in technical and scientific progress and development of society, for a technological economy and in the evolution of modern technological society, information society (digitization, digital signal processing, sensor design, microelectronics, optoelectronics, is based on fundamental phenomena of physics, such as those included in the chapters of optics, quantum physics, physics of nanostructures), respectively the construction of sustainable society, which has become necessary due to the reduction of natural resources and increased pollution , is based on complex physical phenomena, such as those studied in thermodynamics, physics of special materials, semiconductor physics). The answers to fundamental questions in various fields such as medicine, materials science, industry in general, business or politics are in the principles and laws of physics. Science has the potential to be present in building the future to the same extent that it helps to understand the world. (Young & Freedman 2014)